Meta‐analysis of optimal timing of coronary intervention in non‐ST‐elevation acute coronary syndrome. Issue 2 (21st May 2019) - Barbarawi, Mahmoud; Kheiri, Babikir; Zayed, Yazan; Barbarawi, Owais; Chahine, Adam; Haykal, Tarek; Kanugula, Ashok K.; Bachuwa, Ghassan; Alkotob, Mohammad L.; Bhatt, Deepak L.
Abstract: Objectives: We conducted a meta‐analysis of randomized controlled trials (RCTs) to compare the efficacy and safety of early versus delayed invasive management of non‐ST‐elevation acute coronary syndrome (NSTE‐ACS). Background: Coronary angiography is recommended for patients with NSTE‐ACS, however, the optimal timing for this remains controversial. Methods: Literature search of Pubmed/MEDLINE, Cochrane Library, and Embase for all RCTs that compared early with delayed invasive approaches in treating NSTE‐ACS was conducted by two independent authors. Primary outcome was major adverse cardiovascular events (MACE), while the secondary outcomes included cardiovascular mortality, all‐cause mortality, myocardial infarction (MI), and bleeding events. The Mantel‐Haenszel random‐effects model was used to calculate risk ratios (RRs) and 95% confidence intervals (CIs). Results: We included 14 RCTs (9, 637 patients, mean age 65.4, 67% males). The early invasive strategy was associated with a lower incidence of MACE compared with the delayed invasive strategy (RR 0.65, 95%CI 0.49–0.87; p = .003). Subgroup analysis according to GRACE score showed a lower incidence of MACE with early invasive strategies in GRACE >140 patients ( p for interaction = .002). Furthermore, recurrent ischemia was lower in patients with an early invasive strategy (RR 0.42, 95%CI 0.26–0.69; p < .0005). In contrast, there were no significant differences in all‐cause mortality, cardiovascular mortality, MI, or bleeding events between groups (all p > .05). Conclusions: Among patients with NSTE‐ACS, an early invasive strategy was associated with lower incidence of MACE and recurrent ischemia compared with delayed invasive strategy. There were no significant differences in all‐cause mortality, cardiovascular mortality, MI, or bleeding events between groups.